No Evidence for Accelerated Aging-Related Brain Pathology in Treated Human Immunodeficiency Virus: Longitudinal Neuroimaging Results From the Comorbidity in Relation to AIDS (COBRA) Project. (4th January 2018) - Cole, James H; Caan, Matthan W A; Underwood, Jonathan; De Francesco, Davide; van Zoest, Rosan A; Wit, Ferdinand W N M; Mutsaerts, Henk J M M; Leech, Rob; Geurtsen, Gert J; Portegies, Peter; Majoie, Charles B L M; Schim van der Loeff, Maarten F; et al.
Abstract : Longitudinal neuroimaging and neuropsychological assessments were used to study aging-related brain changes in people living with HIV on successful antiretroviral therapy. No differences in brain structure or cognitive function were seen over 2 years, compared to closely matched HIV-negative controls. Abstract: Background: Despite successful antiretroviral therapy, people living with human immunodeficiency virus (PLWH) experience higher rates of age-related morbidity, including abnormal brain structure, brain function, and cognitive impairment. This has raised concerns that PLWH may experience accelerated aging-related brain pathology. Methods: We performed a multicenter longitudinal study of 134 virologically suppressed PLWH (median age, 56.0 years) and 79 demographically similar human immunodeficiency virus (HIV)–negative controls (median age, 57.2 years). To measure cognitive performance and brain pathology, we conducted detailed neuropsychological assessments and multimodality neuroimaging (T1-weighted, T2-weighted, diffusion magnetic resonance imaging [MRI], resting-state functional MRI, spectroscopy, arterial spin labeling) at baseline and at 2 years. Group differences in rates of change were assessed using linear mixed effects models. Results: One hundred twenty-three PLWH and 78 HIV-negative controls completed longitudinal assessments (median interval, 1.97 years). There were no differences between PLWH and HIV-negative controls in age, sex, years of education, smoking or alcohol use. At baseline, PLWH had poorer global cognitive performance ( P < .01), lower gray matter volume ( P = .04), higher white matter hyperintensity load ( P = .02), abnormal white matter microstructure ( P < .005), and greater brain-predicted age difference ( P = .01). Longitudinally, there were no significant differences in rates of change in any neuroimaging measure between PLWH and HIV-negative controls ( P > .1). Cognitive performance was longitudinally stable in both groups. Conclusions: We found no evidence that middle-aged PLWH, when receiving successful treatment, are at increased risk of accelerated aging-related brain changes or cognitive decline over 2 years.